2005
DOI: 10.3748/wjg.v11.i3.407
|View full text |Cite
|
Sign up to set email alerts
|

NOD2/CARD15 gene polymorphism in patients with inflammatory bowel disease: Is Hungary different?

Abstract: AIM:To analyse the impact of NOD2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 24 publications
(42 reference statements)
6
19
2
Order By: Relevance
“…Allele frequency in patients with CD was 15 % compared to 0.83 % in controls. This frequency was similar to that reported in Italians [15] Hungarians [16] and in Croatians [17] CD patients: 10 % 10.8 % and 11.76 % respectively. Lower frequency was reported in Finnish [18] and in Chinese [19] populations 4.8 % and 3.3 % respectively.…”
Section: Frequencies Of Card15 Gene 3020 Insc Mutation and Genotype-psupporting
confidence: 73%
“…Allele frequency in patients with CD was 15 % compared to 0.83 % in controls. This frequency was similar to that reported in Italians [15] Hungarians [16] and in Croatians [17] CD patients: 10 % 10.8 % and 11.76 % respectively. Lower frequency was reported in Finnish [18] and in Chinese [19] populations 4.8 % and 3.3 % respectively.…”
Section: Frequencies Of Card15 Gene 3020 Insc Mutation and Genotype-psupporting
confidence: 73%
“…Need for surgery may be considered a signal of severity, and in this respect our results support the observations that the CARD15 gene plays a role in susceptibility and in the severity of disease as previously reported (21)(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 91%
“…The effect of the CARD15 status on the clinical course of CD was not the focus of the current study, but observations in our three cohorts have shown that the c.3020insC variant is a risk factor for stenotic disease behavior and increases the need for surgical interventions in CD. [6][7][8] Overall, the clinical presentation of IBD was similar among all three populations in terms of age, gender, familial disease, smoking, disease localization, behavior, and surgery.…”
Section: Discussionmentioning
confidence: 81%
“…6 Genotyping for CARD15 variants in CD patients from Nijmegen has been described elsewhere. 7 The analysis stratifies for these three common CARD15 variants.…”
Section: Genotyping For Card15 Variantsmentioning
confidence: 99%